PARTISIPASI ANGGOTA PADA KELOMPOK TANI SUSURIPEN DI KELURAHAN WAILAN KECAMATAN TOMOHON UTARA KOTA TOMOHON - Esti Fanny Pentury; Jenny Baroleh; Welson M. Wangke (AGRI-SOSIOEKONOMI, 2016)
This research has purpose to find out participation of susuripen farmer group’s member in the wailan sub district, north tomohon district, tomohon city. This research been carried out for three months, from April 2016 to June 2016, start from preparation until the prepration of reports. Data used in this research is primary data and secondary data. Primary data obtained from direct interview to the respodents with using questionnaires and secondary data obtained from government agencies which related to the location. Sampling technique used census method with the total of Susuripen farmer groups member is 20 people been interviewed with the questionnaires. Data analysis in this research used descriptive analysis and also likert scale, with level 1 (less active), 2 (active), 3 (very active). This research found based on the analysis using likert scale, that total index of member participation in the Susuripen farmer groups in decision making phase which cover the activeness in the meeting attendance and activeness in the giving opininon. Member participation in the realization activity which covers, activeness in the rice paddy cultivation, activeness in the Horticulture cultivation, activeness in the rice paddy harvest and post-harvest, activeness in the agricultural extension attendance, activeness in the mandatory contribution. Member participation in the evaluation phase which covers involvement in monitoring groups’ activity, involvement in calculating agribusiness outputs. With 79,8 categorized high. Further analysis shows that the member participation level in Susuripen farmer groups with score 479 from presumption that highest score is 600 and lowest score 200. Suggestion in this research based on the summary for the government or locals is motivate member participation in Susuripen farmer groups in the Wailan sub district, north Tomohon district, Tomohon city because that is the main key and main business in the food security development.